Low-Voltage Electrical Installations : (IEC, 2009)
Part 5-56 This part of IEC 60364 coverrs requirements for the selection and erection of low-voltage genrating sets and for the selection and erection of luminaires and lighting instalations intended to be part of the fixed installation